2019
DOI: 10.7554/elife.49175
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Pgk1 enhances neurite outgrowth of motoneurons through Nogo66/NgR-independent targeting of NogoA

Abstract: NogoA inhibits neurite outgrowth of motoneurons (NOM) through interaction with its receptors, Nogo66/NgR. Inhibition of Nogo receptors rescues NOM, but not to the extent exhibited by NogoA-knockout mice, suggesting the presence of other pathways. We found that NogoA-overexpressing muscle cells reduced phosphoglycerate kinase 1 (Pgk1) secretion, resulting in inhibiting NOM. Apart from its glycolytic role and independent of the Nogo66 pathway, extracellular Pgk1 stimulated NOM by triggering a reduction of p-Cofi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
1
23
1
Order By: Relevance
“…Total protein was extracted from embryos and analyzed on 10% SDS-PAGE followed by western blot analysis according to the procedures described by Lin et al [ 16 ], except that the yolk was removed by deyolking buffer (55 mM NaCl, 1.8 mM KCl and 1.25 mM NaHCO 3 ) and antibodies against Flag (Abcam, Cambridge, UK; 1:5000 dilution), α-tubulin (Sigma-Aldrich, St. Louis, MO, USA; 1:5000 dilution), mouse-HRP (Santa Cruz, Santa Cruz, CA, USA; 1:5000 dilution), and rabbit-HRP (Santa Cruz; 1:5000 dilution) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein was extracted from embryos and analyzed on 10% SDS-PAGE followed by western blot analysis according to the procedures described by Lin et al [ 16 ], except that the yolk was removed by deyolking buffer (55 mM NaCl, 1.8 mM KCl and 1.25 mM NaHCO 3 ) and antibodies against Flag (Abcam, Cambridge, UK; 1:5000 dilution), α-tubulin (Sigma-Aldrich, St. Louis, MO, USA; 1:5000 dilution), mouse-HRP (Santa Cruz, Santa Cruz, CA, USA; 1:5000 dilution), and rabbit-HRP (Santa Cruz; 1:5000 dilution) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have unveiled additional abnormalities that may be related to the onset of sporadic and non-SOD1 familial ALS [ 56 ]. These include the impairment of neuronal cytoskeletal function, protein instability, aggregation and degradation of RNA/DNA-binding proteins, and the detrimental roles of non-neuronal cells (such as astrocytes) that can be toxic and degenerative to motor neurons [ 111 ]. Several factors cause difficulty in finding effective therapies for ALS.…”
Section: Neurodegenerative Diseases and Stem Cell Therapy Strategimentioning
confidence: 99%
“…Neuromuscular junction (NMJ) degeneration is the early cytopathy of ALS that directly influences motor function. Reports also suggested that cytopathic cells, motor neurons, and skeletal muscles in the NMJ influenced each other to promote the progression of ALS [96,97]. Thus, NMJ models represent in vitro tools for clarifying the early progression of ALS.…”
Section: Ipscs For Screening Of Therapeutic Compounds For Alsmentioning
confidence: 99%